Mapping hierarchies of mobility in the Baikal Amur Mainline region: a quantitative account of needs and expectations relating to railroad usage - Alexis Sancho-Reinoso (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Gertrude Saxinger (Department of Political Science, Faculty of Social Sciences, University of Vienna); Christoph Fink (Department of Geosciences and Geography, University of Helsinki); Olga Povoroznyuk (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Sigrid Irene Wentzel (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Gertraud Illmeier (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Peter Schweitzer (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Natalia Krasnoshtanova (V.B. Sochava Institute of Geography, Siberian Branch of Russian Academy of Sciences); Vera Kuklina (V.B. Sochava Institute of Geography, Siberian Branch of Russian Academy of Sciences) (Polar Geography, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1625092 The abstract is available here: https://uscholar.univie.ac.at/o:1625092